2022
DOI: 10.1128/msystems.01255-21
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Diversity and Aero-Tolerance in Anammox Bacteria from Geochemically Distinct Aquifers

Abstract: Anammox is increasingly shown to play a major role in the aquatic nitrogen cycle and can outcompete heterotrophic denitrification in environments low in organic carbon. Given that aquifers are characteristically oligotrophic, anammox may represent a major route for the removal of fixed nitrogen in these environments, including agricultural nitrogen, a common groundwater contaminant.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 117 publications
0
28
0
Order By: Relevance
“…Groundwater physicochemical parameters (Table S1 ) were measured as described by Mosley et al [ 30 ] (also see details on methods in Supplementary Materials ). Groundwater and sediment-enriched groundwater from the Canterbury meta-omics series were analyzed for heterotrophic cell counts using pour-plating assays.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Groundwater physicochemical parameters (Table S1 ) were measured as described by Mosley et al [ 30 ] (also see details on methods in Supplementary Materials ). Groundwater and sediment-enriched groundwater from the Canterbury meta-omics series were analyzed for heterotrophic cell counts using pour-plating assays.…”
Section: Methodsmentioning
confidence: 99%
“…Here we tested the prediction that Patescibacteria and DPANN are common to aquifer systems, and transcriptionally active across distinct redox conditions. Given compositional differences reported between planktonic and biofilm fractions of other groundwater prokaryotes [ 30 ], we also determined the compositional, genetic and transcriptional differences between planktonic and sediment-associated ultra-small community fractions. To assess the distribution, metabolic activity and environmental preferences of aquifer microbiomes, we collected 81 groundwater samples from 10 different aquifers spread over hundreds of kilometers [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Groundwater samples were collected from 8 wells from 2 sand/gravel aquifers in Canterbury, New Zealand, as described by (Mosley et al, 2022). Briefly, wells were purged (×3–5 bore volumes), then 3–90 L of groundwater was filtered per sample.…”
Section: Methodsmentioning
confidence: 99%
“…While recent studies have suggested that anammox bacteria are most likely oxygen tolerant rather than strictly anaerobic 53,54 , the comparatively high abundance of anammox in the attached phase could also be due to anaerobic zones deeper in the biofilm. Further, transcriptional activity of anammox genes associated with Brocadia were found in aquifers with anoxic-to-oxic conditions suggesting anammox bacteria are able to contribute to nitrogen loss in a diverse range of oxygen environments 55 .…”
Section: Dissolved Oxygen Dependent Nitrification and Nitrogen Loss O...mentioning
confidence: 99%